2020
DOI: 10.1038/s41401-020-0435-1
|View full text |Cite
|
Sign up to set email alerts
|

Free fatty acid receptor 4 (FFA4) activation ameliorates 2,4-dinitrochlorobenzene-induced atopic dermatitis by increasing regulatory T cells in mice

Abstract: High dose intake of docosahexaenoic acid showed beneficial effects on atopic dermatitis in patients and was found to increase regulatory T cells in mice, but its molecular target has not been identified. Free fatty acid receptor 4 (FFA4, also known as GPR120) is a receptor sensing polyunsaturated long-chain fatty acids including docosahexaenoic acid. In the present study, we examined whether FFA4 acted as a therapeutic target of docosahexaenoic acid for treating atopic dermatitis. Experimental atopic dermatiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…In HFD-fed obese mice, the compound improved glucose tolerance and insulin sensitivity and decreased hyperinsulinemia and hepatic steatosis (Oh et al, 2014 ). Compound A reduced 2,4-dinitrochlorobenzene-induced atopic dermatitis that is mediated through FFA4 receptor activation and Foxp3+ Treg increase in mice (Son et al, 2020 ). However, other studies have suggested that therapies based only on FFA4 receptor activation would not be helpful in the treatment of inflammatory diseases.…”
Section: Long-chain Fatty Acid Receptors In Immune Cellsmentioning
confidence: 99%
“…In HFD-fed obese mice, the compound improved glucose tolerance and insulin sensitivity and decreased hyperinsulinemia and hepatic steatosis (Oh et al, 2014 ). Compound A reduced 2,4-dinitrochlorobenzene-induced atopic dermatitis that is mediated through FFA4 receptor activation and Foxp3+ Treg increase in mice (Son et al, 2020 ). However, other studies have suggested that therapies based only on FFA4 receptor activation would not be helpful in the treatment of inflammatory diseases.…”
Section: Long-chain Fatty Acid Receptors In Immune Cellsmentioning
confidence: 99%
“…Mice lacking Tregs eventually develop autoimmune diseases and allergic symptoms, which indicates that Tregs are necessary for the maintenance of self-tolerance [147][148]. Tregs can prevent the polarisation of Th2 cells by secreting inhibitory cytokines including IL-10, IL-35, and TNF-β, while AD is generally considered a Th2-driven disease [149] Natural polysaccharides have a function of immunostimulating effects and can increase the proportion of Tregs [150]. Polysaccharides from Angelica gigas Nakai (ISAg) induced the polarization of CD4 + T cells toward the acquisition of the Th1 phenotype and the expansion of Treg in Yet40 B6 mice, which suggests that ISAg may be effective for AD therapy [88].…”
Section: Restoring Treg Cell Functionmentioning
confidence: 99%
“…Administration of compound improved glucose tolerance, decreased hyperinsulinemia, increased insulin sensitivity, and decreased hepatic steatosis in obese mice fed a high-fat diet ( Oh et al ., 2014 ). Recently, compound A was used to verify that beneficial effects of DHA on atopic dermatitis is mediated through FFA4 activation and Foxp3 + Treg increase in combination with FFA4 KO mice ( Son et al ., 2020 ).…”
Section: Development Of Synthetic Ffa4 Agonistsmentioning
confidence: 99%